The Trucial Gulf States and Their Role in International Politics - Muhammad Tariq Javed (Britain International for Academic Research (BIAR) Publisher, 2020)
The study focuses on International Relation behavior of Gulf Trucial states seeking security in the wake of perceived regional and international threats. The Gulf States including and other despotic regimes in the region have been found abandoning wider regional Interest and joining Western Power and recently even Israel which is political most contested regime in the region. Gulf States are cluster of small but rich and militarily weaker states. This makes them dependent on big or influential regional and International powers. The personal and despotic family rules in Gulf state have mostly been depended for their sustenance on internationally powerful states for their defense and protection against internal and external threats. The native political movements like Muslim Brotherhood Palestinians who are supported mutually make a case of internal threats for the authoritative and despotic Gulf States Emirates. The movements in Middle East seek wider change on their agenda and the end of concentration of power The study find that personal and despotic rules ignore major political issue and their settlement to sustain their grip on power. This facilitates a short term sustenance at the cost of a bigger regional threat. This political trending of the Gulf States also entails domestic discontent which can sow seeds for future political uncertainties and discontent leading to regional security dilemma and escalated conflicts and confrontations. Paper recommends good relations conditioned with mutual reciprocity and accommodation for sustaining peace in the region to have positive impact on International peace.